THE IMPORTANCE OF REGINONAL REGULATIONS SUPERVISION IN FINANCIAL SECTOR AFTER REGIONAL DEVELOPMENT - Iza Rumesten RS (Faculty of Law, Universitas Jenderal Soedirman, 2015)
Autonomous regional administration may say 80% fail, even many violations in governance can be seen from the many local regulations canceled by the government. The problem of this study is how the regulatory supervision of the financial sector among local parent with a new autonomous regions. Methods used in this research is to examine the normative Law 23 of 2014 and Act No. 17 of 2003. From the results, that local governments still have to master to supervise all local regulations and regulatory policies that made the district / city, especially in the field of finance. An obligation on the parent region to assist funding over three years for new autonomous regions interfere with the delivery system of local governance parent, therefore before diotonomkan, candidates should be prepared to be autonomous administrative regions that after diotonomkan not interfere peyelenggaraan dependent and parent local government. Keywords: finance, authority, local governemnt, supervission.